The Role of the Inflammasome in Heart Failure - Wu, Jimin; Dong, Erdan; Zhang, Youyi; Xiao, Han (Frontiers in Physiology, 2021)
Inflammation promotes the development of heart failure (HF). The inflammasome is a multimeric protein complex that plays an essential role in the innate immune response by triggering the cleavage and activation of the proinflammatory cytokines interleukins (IL)-1β and IL-18. Blocking IL-1β with the monoclonal antibody canakinumab reduced hospitalizations and mortality in HF patients, suggesting that the inflammasome is involved in HF pathogenesis. The inflammasome is activated under various pathologic conditions that contribute to the progression of HF, including pressure overload, acute or chronic overactivation of the sympathetic system, myocardial infarction, and diabetic cardiomyopathy. Inflammasome activation is responsible for cardiac hypertrophy, fibrosis, and pyroptosis. Besides inflammatory cells, the inflammasome in other cardiac cells initiates local inflammation through intercellular communication. Some inflammasome inhibitors are currently being investigated in clinical trials in patients with HF. The current evidence suggests that the inflammasome is a critical mediator of cardiac inflammation during HF and a promising therapeutic target. The present review summarizes the recent advances in both basic and clinical research on the role of the inflammasome in HF.